2021
DOI: 10.14202/vetworld.2021.739-743
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin profiles of animal feeds in the central part of Thailand: 2015-2020

Abstract: Background and Aim: Mycotoxin contamination in animal feeds is of considerable concern because it can affect animal health systems. As a result of contamination in the food chain, humans can indirectly come into contact with mycotoxins. The present study aimed to present mycotoxin contamination patterns in animal feeds from 2015 to 2020 and elucidate associations between the type of feed and the type of ingredient. Materials and Methods: Data were summarized from the records of the Kamphaeng Saen Veterinary D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Bran sample (2 g) was mixed with different sample extraction fluids (20 mL deionised water, 10 mL 70% methanol solution, 8 mL 90% methanol solution, 5 mL 70% methanol solution), respectively, and shaken for 5 min, followed by centrifugation at 2300 g for 10 min. Then, 0.5 mL of the supernatant was used for mycotoxin content measurement by using the corresponding mycotoxin detection kit (deoxynivalenol test kit, aflatoxin B 1 test kit, zearalenone test kit and ochratoxin A test kit) respectively following the manufacturer's instructions (Kananub et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Bran sample (2 g) was mixed with different sample extraction fluids (20 mL deionised water, 10 mL 70% methanol solution, 8 mL 90% methanol solution, 5 mL 70% methanol solution), respectively, and shaken for 5 min, followed by centrifugation at 2300 g for 10 min. Then, 0.5 mL of the supernatant was used for mycotoxin content measurement by using the corresponding mycotoxin detection kit (deoxynivalenol test kit, aflatoxin B 1 test kit, zearalenone test kit and ochratoxin A test kit) respectively following the manufacturer's instructions (Kananub et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…However, rice bran is frequently contaminated with mycotoxins because of the proliferation of toxin-producing fungi at the aleurone layer [5]. In a previous survey of rice bran, detectable levels of mycotoxins, especially those produced by Aspergillus genera [6][7][8] were found, with aflatoxins (AFs) and ochratoxin A (OTA) found at concentrations of up to 28,000 µg•kg −1 and 12,000 µg•kg −1 , respectively [8].…”
Section: Introductionmentioning
confidence: 99%
“…Maize is most commonly contaminated with mycotoxins during production and storage. Aflatoxins, fumonisins (FBs), deoxynivalenol (DON), and zearalenone (ZEN) are the most common mycotoxins found in maize worldwide and are often contaminated simultaneously with various other mycotoxins from Fusarium and Aspergillus species [2,6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Fumonisin B1 (FB1), a toxic secondary metabolite produced by Fusarium verticillioides, widely contaminants maize, wheat, rice and other crops, and is frequently detected in animal feed (Kananub et al, 2021;Li et al, 2015;Park et al, 2017). Although multiple toxicity, the immunotoxicity of FB1 has drawn increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…FB1 pollution in crops is common in east Asia area due to the appropriate climate conditions for mycotoxins formation (Gruber-Dorninger et al, 2019). It was reported that about over 90% maize products and animal feed was contaminated by Fumonisins in China, South Korea and Thailand, though FB1 pollution is common, the contamination level is relatively low and mostly below the limit (Kananub et al, 2021;Li et al, 2015;Park et al, 2017). Due to the wide distribution of FB1 and spreading of CIV, the co-occurrence of FB1 and CIV on the canine is inevitable.…”
Section: Introductionmentioning
confidence: 99%